Impact of invasion into cervical esophagus for patients with hypopharyngeal squamous cell carcinoma. (February 2022) - Chen, Tseng-Cheng; Wang, Chi; Su, Liang-Yen; Lin, Mei-Chun; Yang, Tsung-Lin; Lou, Pei-Jen; Ko, Jenq-Yuh; Wang, Cheng-Ping
Graphical abstract: Highlights: Invasion of cervical esophagus (ICE) is seldom present (13.47%) in HypoSCC. Female gender and HypoSCC in posterior pharyngeal wall were at high risk of ICE. HypoSCC with ICE had significant poorer survival outcome. For HypoSCC without ICE, upfront laryngectomy provided significant benefit. For HypoSCC with ICE, upfront pharyngo-laryngo-esophagectomy had adverse impact. Abstract: Objectives: The invasion into cervical esophagus (ICE) sometimes could be encountered in patients with hypopharyngeal squamous cell carcinoma (HypoSCC). However, the incidence, predictive factors, and prognostic impact of ICE on the patients with HypoSCC remain unclear. Materials and methods: Patient diagnosis with HypoSCC at the National Taiwan University Hospital between January 2007 and December 2018 were reviewed. All patients were classified into two groups: with and without ICE. The curative treatment included upfront laryngectomy or pharyngo-laryngo-esophagectomy (PLE) with adjuvant chemoradiation, or definite organ-sparing chemoradiation. Results: We analyzed 527 HypoSCC patients, 71 (13.47%) with and 456 (86.53%) without ICE. ICE presented more frequently in females (odds ratio (OR) = 3.01, p = 0.03) and posterior pharyngeal wall (OR = 2.34, p = 0.04). The 5-year disease-free survival of patients with and without ICE were 21.7% and 54.1%, respectively (p < 0.0001) and the 5-year overall survival were 13.1% and 53.8%, respectively (p < 0.0001). Among patients with ICE, the disease-free and overall survival of patients with upfront PLE were worse than the patients without upfront PLE (p = 0.21 and p = 0.27, respectively). After multivariant cox analysis, ICE was an independent risk factor for disease-free survival (p < 0.001) and overall survival (p < 0.001). Conclusion: ICE was occasionally present (13.47%) in HypoSCC patients. Unfortunately, the presence of ICE had a significant impact on disease-free and overall survival. For the HypoSCC patients with ICE, organ-sparing chemoradiation should be considered first as upfront PLE had no additional benefit.